German unification in perspective - Paul J. J. Welfens (Intereconomics, 1992)
When German unification took place in 1990, the government was optimistic that the process of closing the economic gap between the two Germanies would be a brief one. However, economic unification has turned out to be more costly and much more complex than anticipated. But on the other hand it is equally true that some problems have been tackled with remarkable success, especially privatization. For the reforming of eastern Europe there are several interesting aspects in these developments.
Keywords: 330; System Transformation